One-component water-based polyurethane adhesive and preparation method thereof

By using castor oil-based polyols and aging-resistant high-viscosity chain extenders and other materials, a single-component water-based polyurethane adhesive was prepared, which solved the problem of insufficient aging resistance and mechanical properties of existing single-component polyurethane adhesives, and achieved higher bonding strength and aging resistance.

CN118291083BActive Publication Date: 2025-04-18广东合力化工科技有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410584028.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-11
Publication Date
2025-04-18
Estimated Expiration
2044-05-11

AI Technical Summary

Technical Problem

The lack of aging resistance and poor mechanical properties of existing one-component polyurethane adhesives limit their application areas.

Method used

The castor oil-based polyol is used as the matrix to synthesize aging-resistant high-viscosity chain extender and react with isophorone diisocyanate and other additives to form an aqueous polyurethane emulsion. Finally, silane coupling agent and modified nanoTiO2 are added. After stirring and vacuum defoaming, a single-component aqueous polyurethane adhesive is prepared.

Benefits of technology

It significantly improves the aging resistance and mechanical properties of the adhesive, enhances its adhesive strength and peel strength, and has a relatively simple process, safe and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention relates to the technical field of chemical adhesives, and discloses a single-component water-based polyurethane adhesive and a preparation method thereof. An aging-resistant high-viscosity chain extender contains a strongly polar dicyano group and a rigid benzene ring structure, which forms a hydrogen bond with carbamate or allophanate, so that the molecular chain changes from a linear shape to a stereotype, the physical crosslinking density increases, and the bonding performance is enhanced; the adhesive itself has a plurality of rigid benzene ring structures with good heat resistance, which can provide strong toughness, and forms a three-dimensional network structure after curing, which can still maintain a relatively stable structure even at high temperatures, thereby enhancing the aging resistance of the adhesive; the modified nano-TiO2 has good compatibility with the polyurethane adhesive, can transmit external stress, offset impact energy, and play a reinforcing effect; an environmentally friendly castor oil-based polyol is used as a matrix, and the chain extender is fixed in the polyurethane adhesive through a chemical reaction, so that no VOC gas is emitted, and the adhesive is green and pollution-free.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical adhesives, in particular to a one-component waterborne polyurethane adhesive and a preparation method thereof. Background Art

[0002] Polyurethane adhesives have excellent properties such as shear resistance, peel resistance, and low temperature resistance, and are suitable for bonding most structural parts. Polyurethane adhesives are divided into two types: single-component and two-component. The polyol and isocyanate components of two-component polyurethane adhesives are stored separately. When used, the two components need to be mixed together in a certain proportion. The gluing process is complicated, errors are prone to occur during mixing, and the labor cost is high. Single-component polyurethane adhesives can undergo cross-linking reactions with water molecules in the air at room temperature and solidify. They are easy to use, have a wide variety, and are widely used, so they have developed rapidly. However, single-component polyurethane adhesives also have disadvantages such as poor aging resistance and mechanical properties. Therefore, modification has become one of the important means to broaden their application areas.

[0003] Waterborne polyurethane adhesives have the advantages of adjustable performance, low temperature resistance, and high bonding strength over traditional waterborne adhesives. Single-component polyurethane adhesives are a type of adhesive that produces viscosity by reacting excess -NCO active groups in the polymer with free active hydrogen in the air or on the substrate, and are supplied to the market in single packages. Patent No. CN113072910B discloses a single-component polyurethane adhesive and a preparation method thereof. An inorganic phase is introduced into the polyurethane system to prepare an organic-inorganic hybrid polyurethane system, thereby improving the mechanical strength and heat resistance of the polyurethane. An epoxy resin is used to modify the organic-inorganic hybrid polyurethane to prepare a single-component high-strength polyurethane adhesive, and the mechanical properties are further improved. However, the preparation process is relatively complicated and does not significantly improve the bonding properties of the adhesive.

[0004] Existing polyurethane adhesives mostly use petroleum polyols, which are non-renewable resources and urgently need to be replaced. my country is rich in oil crop resources, among which castor oil has a high average functionality and a high hydroxyl value content, and can be used as a polyol in the preparation of polyurethane. Compared with conventional polyether polyols and polyester polyols, it has the advantage of being green and environmentally friendly. The present invention uses castor oil polyols to synthesize an aging-resistant high-viscosity chain extender. The active hydrogen-containing substance will replace the unreacted isocyanate group and react with the water molecules in the air first, thereby avoiding the isocyanate group on the molecular chain to react with the water molecules in the air first to produce carbon dioxide. At the same time, the generated alcohol amine or diamine will continue to react with the unreacted isocyanate group to play a role in chain extension, thereby obtaining a water-based polyurethane adhesive with excellent aging resistance and mechanical properties, which is safe and environmentally friendly. Summary of the invention

[0005] The purpose of the present invention is to overcome the deficiencies of the prior art, provide a one-component water-based polyurethane adhesive and a preparation method thereof, and solve the problems of insufficient aging resistance and poor mechanical properties of the existing one-component polyurethane adhesive.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] A method for preparing a one-component waterborne polyurethane adhesive comprises the following steps:

[0008] (1) Castor oil-based polyol is added to a reaction kettle, and distilled under reduced pressure at a temperature of 110-125° C. and a pressure of 0.05-0.08 MPa for 2-4 hours, then cooled to 40-50° C., dibutyltin dilaurate catalyst, trimethylolpropane and isophorone diisocyanate are added, and the temperature is raised to 70-85° C. and reacted for 1-3 hours, and then a 2-hydroxy- ... The aging-resistant high-viscosity chain extender is reacted for 0.5-1h, during which acetone is added to reduce the viscosity, and then the temperature is lowered to 45-55°C, triethylamine is added to adjust the pH to 8-9, deionized water is added, and after stirring evenly, an aqueous polyurethane emulsion is obtained.

[0009] (2) Under a nitrogen atmosphere, add water-based polyurethane emulsion, silane coupling agent and modified nano-TiO2 into a planetary gravity mixer, stir evenly at a speed of 800-1000 r / min, and place in a vacuum degassing machine for vacuum degassing for 120-150 s to obtain a single-component water-based polyurethane adhesive.

[0010] Furthermore, the preparation method of castor oil-based polyol in step (1) comprises the following steps: under a nitrogen atmosphere, adding 100 g of vacuum-dried castor oil and 20-25 g of glycerol into a reaction flask, stirring evenly, adding 0.08-0.12 g of sodium hydroxide catalyst, heating to 170-185° C. for reaction for 2-3 h, and cooling to room temperature to obtain castor oil-based polyol.

[0011] Furthermore, in step (1), the ratio of castor oil-based polyol, dibutyltin dilaurate catalyst, trimethylolpropane, isophorone diisocyanate, aging-resistant high-viscosity chain extender, and deionized water is 100g:(3-5)g:(4-8)g:(20-40)g:(2-6)g:(10-15)g.

[0012] Furthermore, in step (2), the silane coupling agent is any one of 3-aminopropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane or 3-mercaptopropyltriethoxysilane.

[0013] Furthermore, in step (2), the ratio of aqueous polyurethane emulsion, silane coupling agent and modified nano-TiO2 is 100g:(2-4)g:(0.3-1.5)g.

[0014] Furthermore, in step (2), the rotation speed of the vacuum degassing machine is 1500-2000 r / min, and the vacuum degassing time is 120-180 s.

[0015] Furthermore, the preparation method of the aging-resistant high-viscosity chain extender in step (1) comprises the following steps:

[0016] Step S1. Under a nitrogen atmosphere, add bis(4-methoxyphenyl)benzene-1,4-diamine and methanol to a reaction flask equipped with a thermometer and a dropping funnel. After stirring evenly, add acrylonitrile dropwise in an ice-water bath, heat up to react, concentrate under reduced pressure, and purify by column chromatography to obtain bis(4-methoxyphenyl)benzene-1,4-dicyanoethyl.

[0017] Step S2, under a nitrogen atmosphere, add bis(4-methoxyphenyl)benzene-1,4-dicyanoethyl and dichloromethane into a reaction flask equipped with a thermometer and a dropping funnel, stir evenly, then drop boron tribromide, react at 20-35° C. for 12-24 hours, add ethyl acetate and deionized water for extraction, concentrate the organic phase, and dry to obtain an aging-resistant high-viscosity chain extender.

[0018] Furthermore, in step S1, the ratio of bis(4-methoxyphenyl)benzene-1,4-diamine, methanol, and acrylonitrile is 100 g:(1000-1500) mL:(35-45) g.

[0019] Furthermore, in step S1, the reaction temperature is 65-80° C., and the reaction time is 1-3 h.

[0020] Furthermore, in step S2, the ratio of bis(4-methoxyphenyl)benzene-1,4-dicyanoethyl, dichloromethane, and boron tribromide is 100 g:(2000-2500) mL:(145-200) g.

[0021] By adopting the above technical solution, the beneficial effects of the present invention are:

[0022] The invention firstly conducts Michael addition reaction on bis(4-methoxyphenyl)benzene-1,4-diamine and acrylonitrile to obtain bis(4-methoxyphenyl)benzene-1,4-dicyanoethyl, then removes the methoxy group under the action of boron tribromide to obtain an aging-resistant high-viscosity chain extender, then reacts with castor oil-based polyol, isophorone diisocyanate and other additives to obtain an aqueous polyurethane emulsion, finally adds a silane coupling agent and modified nano-TiO2, and obtains a single-component aqueous polyurethane adhesive after stirring and degassing.

[0023] The aging-resistant high-viscosity chain extender contains a strongly polar dicyano group, which forms hydrogen bonds with carbamate or allophanate. The molecular chain gradually changes from linear to three-dimensional, the cross-linking points increase, the physical cross-linking density and cohesive energy increase, and the bonding performance of the adhesive is enhanced; the aging-resistant high-viscosity chain extender itself has 3 benzene rings, which are relatively rigid and can provide strong toughness. When it is copolymerized in the polyurethane molecular chain, extensive hydrogen bonds will be generated. With more hydrogen bonds, the intermolecular force will be strengthened, and the load required for destruction will be greater, thereby significantly improving the peel strength and mechanical strength of the adhesive.

[0024] The aging-resistant high-viscosity chain extender contains a rigid benzene ring and a polar cyano structure, forming a phase region or microphase region inside the polyurethane matrix. The hard segment has a larger polarity and will produce more hydrogen bonds. After curing with the polyurethane system, a three-dimensional network structure is formed. The interaction force between the molecular chains increases accordingly, and it can still maintain a relatively stable structure even at high temperatures, thereby enhancing the aging resistance of the adhesive.

[0025] Modified nano-TiO2 has good compatibility with polyurethane adhesives, can cross-link with terminal isocyanates in adhesives, and act as a filler, which has a thickening effect on adhesives. In polyurethane adhesives, it can not only transmit the external stress it is subjected to well, but also induce the yield of the matrix, offset part of the impact energy, and thus play a role in reinforcing the material; at the same time, silane coupling agent as a small molecule makes the additive easier to be wetted and dispersed more evenly, so that the comprehensive performance of the prepared polyurethane adhesive is more superior.

[0026] The polyurethane adhesive prepared in this experiment uses castor oil-based polyol as the matrix, and does not use other solvents. The aging-resistant high-viscosity chain extender is fixed in the molecular chain of the polyurethane adhesive through chemical reaction, so that it not only has aging-resistant properties, but also has basically no VOC gas emissions, which is in line with the concept of green environmental protection in the modern materials industry. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Preparation of bis(4-methoxyphenyl)benzene-1,4-diamine: Under a nitrogen atmosphere, 236 mg of 4-dibromobenzene and 10 mL of toluene were added to a reaction flask. After stirring evenly, 369 mg of 4-methoxyaniline, 28.8 mg of bis(dibenzylideneacetone)palladium, 8.1 mg of tri-tert-butylphosphine and 288 mg of sodium tert-butoxide were added. The mixture was reacted at 110°C for 12 h, cooled to room temperature, extracted with ethyl acetate and deionized water, and the organic phase was concentrated and dried to obtain bis(4-methoxyphenyl)benzene-1,4-diamine.

[0029] Preparation of modified nano-TiO2: Add 1g nano-TiO2 and 200mL toluene into a reaction flask, stir evenly, then add 0.3mL toluene diisocyanate, react at 110°C for 2h, cool and filter, wash with toluene, and dry to obtain modified nano-TiO2.

[0030] Example 1

[0031] (1) Under nitrogen atmosphere, add 15 g of bis(4-methoxyphenyl)benzene-1,4-diamine and 180 mL of methanol to a reaction flask equipped with a thermometer and a dropping funnel. After stirring evenly, add 6 g of acrylonitrile dropwise in an ice-water bath, react at 70° C. for 2 h, concentrate under reduced pressure, and purify by column chromatography using a mobile system of ethyl acetate and petroleum ether in a ratio of 1:3 to obtain bis(4-methoxyphenyl)benzene-1,4-dicyanoethyl. The preparation reaction formula is as follows:

[0032]

[0033] (2) Under nitrogen atmosphere, 12 g of bis(4-methoxyphenyl)benzene-1,4-dicyanoethyl and 288 mL of dichloromethane were added to a reaction flask equipped with a thermometer and a dropping funnel. After stirring evenly, 18.9 g of boron tribromide was added dropwise. The mixture was reacted at 25° C. for 16 h. Ethyl acetate and deionized water were added for extraction. The organic phase was concentrated and dried to obtain an aging-resistant high-viscosity chain extender. The preparation reaction formula is as follows:

[0034]

[0035] (3) Under a nitrogen atmosphere, 100 g of vacuum-dried castor oil and 22 g of glycerol were added to a reaction flask, stirred evenly, and then 0.1 g of sodium hydroxide catalyst was added. The temperature was raised to 175° C. for reaction for 2 h, and then cooled to room temperature to obtain a castor oil-based polyol.

[0036] (4) 100 g of castor oil-based polyol was added to a reactor and distilled under reduced pressure at a temperature of 115° C. and a pressure of 0.06 MPa for 3 h. The temperature was then lowered to 45° C., 4 g of dibutyltin dilaurate catalyst, 5 g of trimethylolpropane and 3 g of isophorone diisocyanate were added, the temperature was raised to 75° C. and the reaction was continued for 2 h. Subsequently, 2 g of an aging-resistant high-viscosity chain extender was added and the reaction was continued for 1 h. During this period, acetone was added to reduce the viscosity. The temperature was then lowered to 50° C., triethylamine was added to adjust the pH to 9, 12 g of deionized water was added, and the mixture was stirred evenly to obtain an aqueous polyurethane emulsion.

[0037] (5) Under nitrogen atmosphere, 100 g of waterborne polyurethane emulsion, 3.5 g of 3-aminopropyltriethoxysilane and 0.3 g of modified nano-TiO2 were added to a planetary gravity mixer, stirred evenly at a speed of 900 r / min, and then placed in a vacuum degassing machine at a speed of 1800 r / min for vacuum degassing for 150 s to obtain a one-component waterborne polyurethane adhesive.

[0038] Example 2

[0039] (1) Under nitrogen atmosphere, 35 g of bis(4-methoxyphenyl)benzene-1,4-diamine and 350 mL of methanol were added to a reaction flask equipped with a thermometer and a dropping funnel. After stirring evenly, 12.25 g of acrylonitrile was added dropwise in an ice-water bath. The mixture was reacted at 80° C. for 1 h, concentrated under reduced pressure, and purified by column chromatography using a mobile phase of ethyl acetate and petroleum ether in a ratio of 1:3 to obtain bis(4-methoxyphenyl)benzene-1,4-dicyanoethyl.

[0040] (2) Under a nitrogen atmosphere, 25 g of bis(4-methoxyphenyl)benzene-1,4-dicyanoethyl and 500 mL of dichloromethane were added to a reaction flask equipped with a thermometer and a dropping funnel. After stirring evenly, 36.25 g of boron tribromide was added dropwise. The mixture was reacted at 35° C. for 12 h. Ethyl acetate and deionized water were added for extraction. The organic phase was concentrated and dried to obtain an aging-resistant high-viscosity chain extender.

[0041] (3) Under a nitrogen atmosphere, 100 g of vacuum-dried castor oil and 20 g of glycerol were added to a reaction flask, stirred evenly, and then 0.08 g of sodium hydroxide catalyst was added. The temperature was raised to 185° C. for reaction for 2 h, and then cooled to room temperature to obtain a castor oil-based polyol.

[0042] (4) 100 g of castor oil-based polyol was added to a reactor and distilled under reduced pressure at a temperature of 125° C. and a pressure of 0.08 MPa for 2 h. The temperature was then reduced to 50° C., 3 g of dibutyltin dilaurate catalyst, 4 g of trimethylolpropane and 4 g of isophorone diisocyanate were added, the temperature was raised to 85° C. and the reaction was continued for 1 h. Subsequently, 3 g of an aging-resistant high-viscosity chain extender was added and the reaction was continued for 0.5 h. During this period, acetone was added to reduce the viscosity. The temperature was then reduced to 55° C., triethylamine was added to adjust the pH to 8, 10 g of deionized water was added, and the mixture was stirred evenly to obtain an aqueous polyurethane emulsion.

[0043] (5) Under a nitrogen atmosphere, 100 g of an aqueous polyurethane emulsion, 2 g of 3-mercaptopropyltrimethoxysilane, and 0.6 g of modified nano-TiO2 were added to a planetary gravity mixer, stirred evenly at a speed of 1000 r / min, and then placed in a vacuum degassing machine at a speed of 2000 r / min for vacuum degassing for 120 s to obtain a one-component aqueous polyurethane adhesive.

[0044] Example 3

[0045] (1) Under nitrogen atmosphere, 8 g of bis(4-methoxyphenyl)benzene-1,4-diamine and 120 mL of methanol were added to a reaction flask equipped with a thermometer and a dropping funnel. After stirring evenly, 3.6 g of acrylonitrile was added dropwise in an ice-water bath. The mixture was reacted at 65° C. for 3 h, concentrated under reduced pressure, and purified by column chromatography using a mobile phase of ethyl acetate and petroleum ether in a ratio of 1:3 to obtain bis(4-methoxyphenyl)benzene-1,4-dicyanoethyl.

[0046] (2) Under nitrogen atmosphere, 5 g of bis(4-methoxyphenyl)benzene-1,4-dicyanoethyl and 125 mL of dichloromethane were added to a reaction flask equipped with a thermometer and a dropping funnel. After stirring evenly, 10 g of boron tribromide was added dropwise. The mixture was reacted at 20° C. for 24 h. Ethyl acetate and deionized water were added for extraction. The organic phase was concentrated and dried to obtain an aging-resistant high-viscosity chain extender.

[0047] (3) Under a nitrogen atmosphere, 100 g of vacuum-dried castor oil and 25 g of glycerol were added to a reaction flask, stirred evenly, and then 0.12 g of sodium hydroxide catalyst was added. The temperature was raised to 170° C. for reaction for 3 h, and then cooled to room temperature to obtain a castor oil-based polyol.

[0048] (4) 100 g of castor oil-based polyol was added to a reactor and distilled under reduced pressure at a temperature of 110° C. and a pressure of 0.05 MPa for 4 h. The temperature was then reduced to 40° C., 5 g of dibutyltin dilaurate catalyst, 8 g of trimethylolpropane and 2 g of isophorone diisocyanate were added, the temperature was raised to 70° C. and the reaction was continued for 3 h. Subsequently, 4 g of an aging-resistant high-viscosity chain extender was added and the reaction was continued for 1 h. During this period, acetone was added to reduce the viscosity. The temperature was then reduced to 45° C., triethylamine was added to adjust the pH to 9, 15 g of deionized water was added, and the mixture was stirred evenly to obtain an aqueous polyurethane emulsion.

[0049] (5) Under nitrogen atmosphere, 100 g of waterborne polyurethane emulsion, 4 g of 3-mercaptopropyltriethoxysilane and 0.9 g of modified nano-TiO2 were added to a planetary gravity mixer, stirred evenly at a speed of 800 r / min, and then placed in a vacuum degassing machine at a speed of 1500 r / min for vacuum degassing for 180 s to obtain a one-component waterborne polyurethane adhesive.

[0050] Example 4

[0051] (1) Under nitrogen atmosphere, 18 g of bis(4-methoxyphenyl)benzene-1,4-diamine and 215 mL of methanol were added to a reaction flask equipped with a thermometer and a dropping funnel. After stirring evenly, 8 g of acrylonitrile was added dropwise in an ice-water bath. The mixture was reacted at 75° C. for 3 h, concentrated under reduced pressure, and purified by column chromatography using a mobile phase of ethyl acetate and petroleum ether in a ratio of 1:3 to obtain bis(4-methoxyphenyl)benzene-1,4-dicyanoethyl.

[0052] (2) Under a nitrogen atmosphere, 10 g of bis(4-methoxyphenyl)benzene-1,4-dicyanoethyl and 215 mL of dichloromethane were added to a reaction flask equipped with a thermometer and a dropping funnel. After stirring, 16 g of boron tribromide was added dropwise. The mixture was reacted at 25° C. for 15 h. Ethyl acetate and deionized water were added for extraction. The organic phase was concentrated and dried to obtain an aging-resistant high-viscosity chain extender.

[0053] (3) Under a nitrogen atmosphere, 100 g of vacuum-dried castor oil and 23 g of glycerol were added to a reaction flask, stirred evenly, and then 0.11 g of sodium hydroxide catalyst was added. The temperature was raised to 180° C. for reaction for 3 h, and then cooled to room temperature to obtain a castor oil-based polyol.

[0054] (4) 100 g of castor oil-based polyol was added to a reactor and distilled under reduced pressure at a temperature of 115° C. and a pressure of 0.07 MPa for 3 h. The temperature was then reduced to 45° C., 5 g of dibutyltin dilaurate catalyst, 5 g of trimethylolpropane and 3 g of isophorone diisocyanate were added, the temperature was raised to 80° C. and the reaction was continued for 2 h. Then 5 g of an aging-resistant high-viscosity chain extender was added and the reaction was continued for 1 h. During this period, acetone was added to reduce the viscosity. The temperature was then reduced to 50° C., triethylamine was added to adjust the pH to 9, 12 g of deionized water was added, and the mixture was stirred evenly to obtain an aqueous polyurethane emulsion.

[0055] (5) Under nitrogen atmosphere, 100 g of waterborne polyurethane emulsion, 3 g of 3-aminopropyltriethoxysilane and 1.2 g of modified nano-TiO2 were added to a planetary gravity mixer, stirred evenly at a speed of 850 r / min, and then placed in a vacuum degassing machine at a speed of 1900 r / min for vacuum degassing for 160 s to obtain a one-component waterborne polyurethane adhesive.

[0056] Example 5

[0057] (1) Under nitrogen atmosphere, 20 g of bis(4-methoxyphenyl)benzene-1,4-diamine and 275 mL of methanol were added to a reaction flask equipped with a thermometer and a dropping funnel. After stirring evenly, 6.4 g of acrylonitrile was added dropwise in an ice-water bath. The mixture was reacted at 70° C. for 3 h, concentrated under reduced pressure, and purified by column chromatography using a mobile phase of ethyl acetate and petroleum ether in a ratio of 1:3 to obtain bis(4-methoxyphenyl)benzene-1,4-dicyanoethyl.

[0058] (2) Under a nitrogen atmosphere, 9 g of bis(4-methoxyphenyl)benzene-1,4-dicyanoethyl and 190 mL of dichloromethane were added to a reaction flask equipped with a thermometer and a dropping funnel. After stirring evenly, 14.8 g of boron tribromide was added dropwise. The mixture was reacted at 30° C. for 16 h. Ethyl acetate and deionized water were added for extraction. The organic phase was concentrated and dried to obtain an aging-resistant high-viscosity chain extender.

[0059] (3) Under a nitrogen atmosphere, 100 g of vacuum-dried castor oil and 25 g of glycerol were added to a reaction flask, stirred evenly, and then 0.08 g of sodium hydroxide catalyst was added. The temperature was raised to 175° C. for reaction for 3 h, and cooled to room temperature to obtain castor oil-based polyol.

[0060] (4) 100 g of castor oil-based polyol was added to a reactor and distilled under reduced pressure at a temperature of 120° C. and a pressure of 0.05 MPa for 4 h. The temperature was then reduced to 50° C., 3.5 g of dibutyltin dilaurate catalyst, 5.2 g of trimethylolpropane and 3.6 g of isophorone diisocyanate were added, the temperature was raised to 80° C. and the reaction was continued for 2 h. Subsequently, 6 g of an aging-resistant high-viscosity chain extender was added and the reaction was continued for 1 h. During this period, acetone was added to reduce the viscosity. The temperature was then reduced to 50° C., triethylamine was added to adjust the pH to 9, 13 g of deionized water was added, and the mixture was stirred evenly to obtain an aqueous polyurethane emulsion.

[0061] (5) Under nitrogen atmosphere, 100 g of waterborne polyurethane emulsion, 2.5 g of 3-mercaptopropyltrimethoxysilane and 1.5 g of modified nano-TiO2 were added to a planetary gravity mixer, stirred evenly at a speed of 1000 r / min, and then placed in a vacuum degassing machine at a speed of 1800 r / min for vacuum degassing for 150 s to obtain a one-component waterborne polyurethane adhesive.

[0062] Comparative Example 1

[0063] (1) Under nitrogen atmosphere, 12 g of bis(4-methoxyphenyl)benzene-1,4-diamine and 288 mL of dichloromethane were added to a reaction flask equipped with a thermometer and a dropping funnel. After stirring, 18.9 g of boron tribromide was added dropwise. The mixture was reacted at 25° C. for 16 h. Ethyl acetate and deionized water were added for extraction. The organic phase was concentrated and dried to obtain a chain extender having the structural formula:

[0064] (2) 100 g of castor oil-based polyol (prepared in Example 1) was added to a reactor and distilled under reduced pressure at a temperature of 115° C. and a pressure of 0.06 MPa for 3 h. The temperature was then lowered to 45° C., 4 g of dibutyltin dilaurate catalyst, 5 g of trimethylolpropane and 3 g of isophorone diisocyanate were added, the temperature was raised to 75° C. and the reaction was continued for 2 h. Subsequently, 2 g of a chain extender was added and the reaction was continued for 1 h. During this period, acetone was added to reduce the viscosity. The temperature was then lowered to 50° C., triethylamine was added to adjust the pH to 9, 12 g of deionized water was added, and the mixture was stirred evenly to obtain an aqueous polyurethane emulsion.

[0065] (3) Under nitrogen atmosphere, 100 g of waterborne polyurethane emulsion, 3.5 g of 3-aminopropyltriethoxysilane and 0.3 g of modified nano-TiO2 were added to a planetary gravity mixer, stirred evenly at a speed of 900 r / min, and then placed in a vacuum degassing machine at a speed of 1800 r / min for vacuum degassing for 150 s to obtain a one-component waterborne polyurethane adhesive.

[0066] Comparative Example 2

[0067] (1) Under nitrogen atmosphere, 15 g of diethanolamine and 180 mL of methanol were added to a reaction flask equipped with a thermometer and a dropping funnel. After stirring evenly, 6 g of acrylonitrile was added dropwise in an ice-water bath. The mixture was reacted at 70° C. for 2 h, concentrated under reduced pressure, and purified by column chromatography using a mobile phase of ethyl acetate and petroleum ether in a ratio of 1:3 to obtain N-(2-cyanoethyl)diethanolamine, the structural formula of which is

[0068] (2) 100 g of castor oil-based polyol was added to a reactor and distilled under reduced pressure at a temperature of 115° C. and a pressure of 0.06 MPa for 3 h. The temperature was then lowered to 45° C., 4 g of dibutyltin dilaurate catalyst, 5 g of trimethylolpropane and 3 g of isophorone diisocyanate were added, the temperature was raised to 75° C. and the reaction was continued for 2 h. Subsequently, 2 g of N-(2-cyanoethyl)diethanolamine was added and the reaction was continued for 1 h. During this period, acetone was added to reduce the viscosity. The temperature was then lowered to 50° C., triethylamine was added to adjust the pH to 9, 12 g of deionized water was added, and the mixture was stirred evenly to obtain an aqueous polyurethane emulsion.

[0069] (3) Under nitrogen atmosphere, 100 g of waterborne polyurethane emulsion, 3.5 g of 3-aminopropyltriethoxysilane and 0.3 g of modified nano-TiO2 were added to a planetary gravity mixer, stirred evenly at a speed of 900 r / min, and then placed in a vacuum degassing machine at a speed of 1800 r / min for vacuum degassing for 150 s to obtain a one-component waterborne polyurethane adhesive.

[0070] Comparative Example 3

[0071] (1) 100 g of castor oil-based polyol was added to a reactor and distilled under reduced pressure at a temperature of 115° C. and a pressure of 0.06 MPa for 3 h. The temperature was then lowered to 45° C., 4 g of dibutyltin dilaurate catalyst, 5 g of trimethylolpropane and 3 g of isophorone diisocyanate were added, the temperature was raised to 75° C. and the reaction was continued for 2 h. Subsequently, 2 g of 1,4-butanediol was added and the reaction was continued for 1 h. During this period, acetone was added to reduce the viscosity. The temperature was then lowered to 50° C., triethylamine was added to adjust the pH to 9, 12 g of deionized water was added, and the mixture was stirred evenly to obtain an aqueous polyurethane emulsion.

[0072] (2) Under a nitrogen atmosphere, 100 g of an aqueous polyurethane emulsion and 3.5 g of tri-aminopropyltriethoxysilane were added to a planetary gravity mixer, stirred evenly at a speed of 900 r / min, and then placed in a vacuum degassing machine at a speed of 1800 r / min for vacuum degassing for 150 s to obtain a one-component aqueous polyurethane adhesive.

[0073] Viscosity test of adhesive: refer to GB / T 2794-2013 national standard, use rotational viscometer to measure the viscosity of the product, the test temperature is 25℃, and the rotation speed of the rotational viscometer is 10r / min.

[0074] Table 1 Adhesive viscosity test results

[0075] Viscosity (mpa·s) Example 1 7250 Example 2 8180 Example 3 8960 Example 4 10070 Example 5 10910 Comparative Example 1 5960 Comparative Example 2 7080 Comparative Example 3 4850

[0076] It can be seen from the test results in the above table that with the increase of the content of the aging-resistant high-viscosity chain extender in the polyurethane adhesive, the viscosity of the adhesive gradually increases. The viscosity in Example 5 reaches 10910 MPa·s, and the bonding strength is significantly improved. This is because, on the one hand, the aging-resistant high-viscosity chain extender contains a strongly polar dicyano group, which forms a hydrogen bond with carbamate or allophanate, thereby causing an increase in the physical crosslinking density, thereby enhancing the polarity of the polyurethane, and the molecular chain gradually changes from a linear shape to a stereotype, with an increase in the crosslinking points and a gradual increase in the cohesive energy, which promotes the enhancement of the bonding performance of the adhesive; on the other hand, because the modified nano-TiO2 has good compatibility with the polyurethane adhesive, it can be cross-linked with the terminal isocyanate in the adhesive, and act as a filler, which has a thickening effect on the adhesive, resulting in an increase in the viscosity of the adhesive system. At the same time, the silane coupling agent, as a small molecule, makes the additive easier to be wetted, dispersed more evenly, and the viscosity is further increased.

[0077] Comparative Example 1 does not contain a cyano group, which does not increase the physical crosslinking density of the adhesive, so the viscosity is only 5960 MPa·s; Comparative Example 2 contains a cyano group, which can form hydrogen bonds with carbamate or allophanate, and the adhesion of the adhesive is higher than that of Comparative Example 1; Comparative Example 3 does not contain a cyano group or modified nano-TiO2, and its adhesion performance is the worst.

[0078] T-peel strength test: Referring to the standard GB / T 2791-1995, 0.5g of the prepared adhesive was evenly applied to a 25cm×3cm PVC strip, and then placed to dry naturally, hot pressed at 80℃, and then the peel strength was tested using an electronic universal testing machine, with a tensile speed of 100mm / min, repeated 5 times, and the average value was taken.

[0079] Table 2 Adhesive peel strength test results

[0080] T-peel strength (N / cm) Example 1 20.55 Example 2 23.37 Example 3 26.62 Example 4 30.10 Example 5 28.93 Comparative Example 1 14.64 Comparative Example 2 18.12 Comparative Example 3 13.26

[0081] Polarity is an important factor affecting the bonding strength of adhesives to polar substrates. The stronger the polarity of the adhesive, the better the polar bonding effect. It can be seen from the test results in the above table that with the increase of the content of aging-resistant high-viscosity chain extender in the polyurethane adhesive, the peel strength of the adhesive gradually increases. This is because the polarity of the dicyano group in the aging-resistant high-viscosity chain extender is relatively strong, which increases the polarity of the polyurethane system and increases the bonding strength to PVC. At the same time, the aging-resistant high-viscosity chain extender itself has 3 benzene rings, which are relatively rigid and can provide strong toughness. When it is copolymerized in the polyurethane molecular chain, it will produce extensive hydrogen bonds, increase the number of hydrogen bonds, and strengthen the intermolecular force, thereby significantly improving the peel strength of the adhesive.

[0082] Preparation of adhesive film: Place the prepared polyurethane adhesive on a polytetrafluoroethylene plate with a frame sprayed with a release agent, place it horizontally, dry it naturally, and place it at room temperature for 2 weeks before cutting it into dumbbell-shaped specimens to test its performance.

[0083] Tensile performance test: refer to standard GB / T 528-2009, use electronic universal testing machine for testing, tensile speed is 50mm / min, test temperature is 25℃.

[0084] Shore hardness test: Tested in accordance with standard GB / T 531-2008.

[0085] Table 3 Mechanical properties test results of adhesives

[0086] Tensile strength(MPa) Shore Hardness(HA) Example 1 8.5 70 Example 2 9.2 75 Example 3 10.1 78 Example 4 10.6 82 Example 5 9.9 83 Comparative Example 1 7.5 61 Comparative Example 2 6.3 53 Comparative Example 3 5.6 48

[0087] It can be seen from the test results in the above table that with the increase of the content of aging-resistant high-viscosity chain extender in the polyurethane adhesive, the mechanical properties of the adhesive gradually increase. This is because the aging-resistant high-viscosity chain extender contains a rigid benzene ring structure, and the urea bonds generated with the isocyanate groups in the polyurethane system increase, which increases the cross-linking density of the system. The greater the load required for destruction, the more obvious the improvement in its mechanical properties; at the same time, the increase in the amount of modified nano-TiO2 added in the polyurethane adhesive can not only well transmit the external stress it is subjected to, but also induce the yield of the matrix, offset part of the impact energy, and thus play the effect of material reinforcement.

[0088] Aging resistance test: Tested in accordance with standard GB / T 3512-2001, aging conditions are 150℃×168h.

[0089] Table 4 Test results of aging resistance of adhesive

[0090]

[0091]

[0092] It can be seen from the test results in the above table that with the increase of the content of aging-resistant high-viscosity chain extender in the polyurethane adhesive, the aging resistance of the adhesive gradually increases. After being placed at 150°C for 168 hours, the tensile strength and Shore hardness values ​​of the adhesive do not change much. This is because the aging-resistant high-viscosity chain extender contains a rigid benzene ring structure, which forms a phase region or microphase region inside the polyurethane matrix. The polarity of the hard segment is relatively large, and more hydrogen bonds will be generated between them. After curing with the polyurethane system, a three-dimensional network structure is formed. The interaction force between the molecular chains increases accordingly, and a relatively stable structure can be maintained even at high temperatures, thereby enhancing the aging resistance of the adhesive.

[0093] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, and these simple modifications all belong to the protection scope of the present invention. It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

Claims

1. A method for preparing a one-component waterborne polyurethane adhesive, characterized in that: The preparation method comprises the following steps: (1) Castor oil-based polyol is added to a reactor, and distilled under reduced pressure at a temperature of 110-125°C and a pressure of 0.05-0.08 MPa for 2-4 hours, then cooled to 40-50°C, and dibutyltin dilaurate catalyst, trimethylolpropane and isophorone diisocyanate are added, and the temperature is raised to 70-85°C and reacted for 1-3 hours, and then a compound with the structural formula The aging-resistant high-viscosity chain extender is added, and the reaction is continued for 0.5-1h, during which acetone is added to reduce the viscosity, and then the temperature is lowered to 45-55°C, triethylamine is added to adjust the pH to 8-9, and deionized water is added. After stirring evenly, an aqueous polyurethane emulsion is obtained; (2) Under a nitrogen atmosphere, adding waterborne polyurethane emulsion, silane coupling agent and modified nano-TiO2 into a planetary gravity mixer, stirring evenly at a speed of 800-1000 r / min, and placing in a vacuum degassing machine for vacuum degassing to obtain a single-component waterborne polyurethane adhesive; The method for preparing castor oil-based polyol in step (1) comprises the following steps: adding 100 g of vacuum-dried castor oil and 20-25 g of glycerol into a reaction flask under a nitrogen atmosphere, stirring evenly, adding 0.08-0.12 g of sodium hydroxide catalyst, heating to 170-185° C. for reaction for 2-3 h, and cooling to room temperature to obtain castor oil-based polyol; In the step (1), the ratio of castor oil-based polyol, dibutyltin dilaurate catalyst, trimethylolpropane, isophorone diisocyanate, aging-resistant high-viscosity chain extender, and deionized water is 100 g: (3-5) g: (4-8) g: (20-40) g: (2-6) g: (10-15) g; In step (2), the silane coupling agent is any one of 3-aminopropyltriethoxysilane, 3-mercaptopropyltrimethoxysilane or 3-mercaptopropyltriethoxysilane; In the step (2), the ratio of the aqueous polyurethane emulsion, the silane coupling agent, and the modified nano-TiO2 is 100 g: (2-4) g: (0.3-1.5) g; In step (2), the speed of the vacuum degassing machine is 1500-2000 r / min, and the vacuum degassing time is 120-180 s; The preparation method of modified nano-TiO2 in step (2) comprises the following steps: adding 1g nano-TiO2 and 200mL toluene into a reaction flask, stirring evenly, adding 0.3mL toluene diisocyanate, reacting at 110°C for 2h, cooling and filtering, washing with toluene, and drying to obtain modified nano-TiO2.

2. The method for preparing the one-component waterborne polyurethane adhesive according to claim 1, characterized in that: The method for preparing the aging-resistant high-viscosity chain extender in step (1) comprises the following steps: Step S1, under a nitrogen atmosphere, add bis(4-methoxyphenyl)benzene-1,4-diamine and methanol to a reaction flask equipped with a thermometer and a dropping funnel, stir evenly, then dropwise add acrylonitrile in an ice-water bath, heat to react, concentrate under reduced pressure, and purify by column chromatography to obtain bis(4-methoxyphenyl)benzene-1,4-dicyanoethyl; Step S2, under a nitrogen atmosphere, add bis(4-methoxyphenyl)benzene-1,4-dicyanoethyl and dichloromethane to a reaction flask equipped with a thermometer and a dropping funnel, stir evenly, drop boron tribromide, react at 20-35° C. for 12-24 hours, add ethyl acetate and deionized water for extraction, concentrate the organic phase, and dry to obtain an aging-resistant high-viscosity chain extender.

3. The method for preparing the one-component waterborne polyurethane adhesive according to claim 2, characterized in that: In the step S1, the ratio of bis(4-methoxyphenyl)benzene-1,4-diamine, methanol and acrylonitrile is 100 g: (1000-1500) mL: (35-45) g.

4. The method for preparing the one-component waterborne polyurethane adhesive according to claim 2, characterized in that: In step S1, the reaction temperature is 65-80° C. and the reaction time is 1-3 h.

5. The method for preparing the one-component waterborne polyurethane adhesive according to claim 2, characterized in that: In the step S2, the ratio of bis(4-methoxyphenyl)benzene-1,4-dicyanoethyl, dichloromethane, and boron tribromide is 100 g: (2000-2500) mL: (145-200) g.

Citation Information

Patent Citations

  • A one-component polyurethane adhesive and its preparation method

    CN113072910B

  • Waterborne polyurethane adhesive and preparation method thereof

    CN101962524A

  • Water-resistant high-temperature-resistant single-component waterborne polyurethane adhesive and preparation method thereof

    CN108342181A